Diversification of Potato-based Cropping Systems in Red and Lateritic Soils of West Bengal for Enhanced Productivity, Profitability and Resource Use Efficiency - Kumar, Basant; Barik, Arun Kumar; Saha, Somnath; Fatima, Ayesha (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted at Agricultural farm of the Institute during 2020–21 and 2021–22 to assess the productivity and profitability of various potato-based cropping sequences in red and lateritic soil of West Bengal. Seven cropping sequences, viz., potato-sesame; potato-greengram; potato–babycorn; potato-okra; potato-groundnut; potato-blackgram and potato-vegetable cowpea was evaluated in randomized block design with three replications. Potato-vegetable cowpea sequence recorded significantly higher system productivity (47.47 t ha-1) and system production efficiency (130.05 kg ha-1 day-1) than all other cropping sequences. The system productivity and production efficiency of potato-babycorn sequence were comparable with potato–groundnut sequence but were significantly higher than potato-okra, potato-greengram, potato-sesame and potato-blackgram sequences. The potato-greengram sequence registered the highest employment generation (142-man days ha-1) whereas the potato-vegetable cowpea sequence and potato-okra sequence recorded the highest land use efficiency (59.86%). The gross return (493×103 ` ha-1) and net return (365×103 ` ha-1) was found to be highest in potato-vegetable cowpea sequence over other potato-based cropping sequences. The highest return per rupee invested (3.86) and system economic efficiency (1017×103 ` ha-1) was achieved in potato-vegetable cowpea which was followed by potato-groundnut sequence. Thus, among the seven potato-based cropping sequences, it was revealed that potato-vegetable cowpea sequence had the highest system productivity, production efficiency, gross return, net return, return per rupee invested and land use efficiency in red and lateritic soil of West Bengal.